Comparison of crop, fisheries and livestock information displayed on agriculture websites - Ramli, Nor Sabila; Hassan, Md. Salleh; Abu Samah, Bahaman; Shahkat Ali, Muhamad Sham (TextRoad Publication, 2013)
The swift evolution of information technology has doubtlessly profiteda number of industries within this country, of which agriculture is one. The existence of new and developing technologies has greatly assisted agriculture, and the term ‘modern agriculture’ entails the extensive technology used to enhance the quantity and quality of agriculture productivity. One of the most important technologies employed is the Internet, and the main attempt of this paper is to evaluate the information contained on agriculture websites. The data for this study was gained using content analysis on 27 selected agriculture websites maintained by a number of government agencies. The websites were divided into three groups,namely Department of Agriculture, Department of Fisheries and Department of Veterinary Services. The findings conclude that each website has its own unique identity,while displaying information with regards to the expertise of the organization behind the site. Further analyses confirm that information with regards to highly potential crops/fisheries/livestock, available courses and financial information are highly sought after by users. To further improve the websites, issues with regards to a lack of technical agricultural technical information should be addressed.